Functional regulation of PI3K-associated signaling in the accumbens by binge alcohol drinking in male but not female mice. (June 2016) - Cozzoli, Debra K.; Kaufman, Moriah N.; Nipper, Michelle A.; Hashimoto, Joel G.; Wiren, Kristine M.; Finn, Deborah A.
Abstract: It is well established that binge alcohol consumption produces alterations in Group 1 metabotropic glutamate receptors (mGlus) and related signaling cascades in the nucleus accumbens (NAC) of adult male mice, but female and adolescent mice have not been examined. Thus, the first set of studies determined whether repeated binge alcohol consumption produced similar alterations in protein and mRNA levels of Group 1 mGlu-associated signaling molecules in the NAC of male and female adult and adolescent mice. The adult (9 weeks) and adolescent (4 weeks) C57BL/6J mice were exposed to 7 binge alcohol sessions every 3rd day while controls drank water. Repeated binge alcohol consumption produced sexually divergent changes in protein levels and mRNA expression for Group 1 mGlus and downstream signaling molecules in the NAC, but there was no effect of age. Binge alcohol intake decreased mGlu5 levels in females, whereas it decreased indices of phosphoinositide 3-kinase (PI3K), mammalian target of rapamycin (mTOR), 4E-binding protein 1, and p70 ribosomal protein S6 kinase in males. Expression of genes encoding mGlu1, mGlu5, the NR2A subunit of the NMDA receptor, and Homer2 were all decreased by binge alcohol consumption in males, while females were relatively resistant (only phosphoinositide-dependent protein kinase 1 was decreased). The functional implication of these differences was investigated in a separate study by inhibiting mTOR in the NAC (via infusions of rapamycin) before binge drinking sessions. Rapamycin (50 and 100 ng/side) significantly decreased binge alcohol consumption in males, while consumption in females was unaffected. Altogether these results highlight that mTOR signaling in the NAC was necessary to maintain binge alcohol consumption only in male mice and that binge drinking recruits sexually divergent signaling cascades downstream of PI3K and presumably, Group 1 mGlus. Importantly, these findings emphasize that sex should be considered in the development of potential pharmacotherapeutic targets. Highlights: Binge drinking recruits sexually divergent signaling cascades in the accumbens. Intra-accumbens rapamycin decreases binge drinking only in male mice. Binge drinking decreased PI3K signaling in the accumbens only in male mice. Age did not alter sex differences in accumbens signaling after binge drinking.